A De Novo Synthetic Route to 1,2,3,4-Tetrahydroisoquinoline Derivatives - Ábrahámi, Renáta A.; Fustero, Santos; Fülöp, Ferenc; Kiss, Loránd (Synlett, 2018)
A novel synthetic approach was developed for the construction of the 1,2,3,4-tetrahydroisoquinoline framework possessing varied functions. The synthetic strategy was based on oxidative ring opening of some indene derivatives through their C=C bond, followed by double reductive amination of the dicarbonyl intermediates with various primary alkyl- or fluoroalkylamines.
Keywords: tetrahydroisoquinolines; ring opening; ring closure; reduction; amination; fluorination